The Impact of Fiscal Policy on the Sustainable Development of China’s Photovoltaic Industry - Tong, Xin; You, Mingyang; Gu, Liangjie (Frontiers in Environmental Science, 2022)
This paper is to study the progressive impact of China's fiscal policy on the sustainable development of the photovoltaic industry. On the one hand, the method based on characteristic facts, through the derivation of the evolutionary game theory of the two parties, finds the influence of the central and the local government on the alternate development of China's photovoltaic industry production enterprises and power generation enterprises due to different policy subjects; on the other hand, based on the From 2013 to 2018, the newly installed capacity of distributed photovoltaics in various provinces in China, through the method of measurement and empirical evidence, found that policy preferences (policy objects, methods, links, timing and intensity, etc.) the effects of alternate development. This paper believes that in terms of policy subjects, the central government should be the mainstay of the power generation, while in the production, considering the impact of the new crown epidemic and upstream raw materials, the joint efforts of the central and local governments are needed; and in terms of policy preferences, the Chinese government needs to give greater policy support to distributed photovoltaics in order to achieve carbon peaking in 2030 and carbon neutrality in 2060, which should not be interrupted by policies such as "whole county development" and "building surface photovoltaics".